Facial Trauma Caused by Firearm: Literature Review - Moreschi, Eduardo (2009)
The facial injuries are relatively frequent, which may be the result of car accidents, sports and physical aggression, where various types of causative agents may be involved, among them the firearms. The fractures in the face from a firearm are caused by a variety of weapons. Wounds on the face from a firearm can cause total destruction of tissues. However, the immediate treatment of the wound reduces the effect of morbidity, with a significant number of patients require more extensive reconstructive procedures. As the prosthetics rehabilitation almost always necessary. This study aimed to demonstrate through a literature review, the features and options for treatment of facial trauma caused by a firearm.